Youth Mosque Activities as a Means of Youth Empowerment at Masjid Ar-Raudhah, Bambu Kuning - Anggi Pratiwi; Rahma Anggi Pratiwi; Wulan Afirli; Rika Fitri Ramadani (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Mosque youth activities are one form of youth development that plays an important role in improving the spiritual, social, and leadership qualities of adolescents amid the challenges of modern development. This study aims to analyze the role of mosque youth activities as a means of youth empowerment at Masjid Ar-Raudhah, Bambu Kuning. The method used was a qualitative approach with data collection techniques through observation, interviews, and documentation involving mosque youth administrators and members. The results of the study indicate that various activities such as regular religious studies, leadership training, social activities, and commemorations of Islamic holidays were able to enhance religious understanding, social skills, and the sense of responsibility among adolescents. In addition, these activities also served as a medium for character building and diverting youth from negative environmental influences. However, the implementation still faced obstacles in the form of limited facilities and the low participation of some adolescents. Therefore, it can be concluded that mosque youth activities have a strategic role in youth empowerment, and continuous support from mosque administrators and the community is needed to optimize their implementation.